The role of teaching presence and student participation in Spanish blended courses. Issue 3 (4th March 2018) - Rubio, Fernando; Thomas, Jonathan M.; Li, Qin
ABSTRACT: This chapter describes a study of a blended language course that combines face-to-face (F2F) instructional time with an online component. The purpose of the study is to understand how teachers and students exploit the complementarity of the two delivery formats to improve the learning experience. The study first examines how the presence of an online component affects the F2F portion of the course by comparing it to a corresponding section of the same course taught entirely F2F. The findings of this first part of the study show major differences between the two delivery formats regarding teaching strategies and teaching presence. The second part of the study uses LMS data to analyze student participation in the online component of the blended course. Data were gathered to measure active participation, passive participation and continuity. The results show that online behaviors distinguish less successful students from more successful ones, and that there is a strong correlation between low levels of online participation and low grades in the course. Continuity proved to be the strongest predictor variable for success in the course. The results have important implications for course design and the use of learning analytics for the early identification of at-risk students.